Effect of two surgical field antisepsis protocols on the reduction of number of skin bacteria in bovines undergoing field reproductive surgeries - González V., Roger (2023)
The effect of two surgical field antisepsis protocols on the reduction of the number of skin bacteria in bovines subjected to field reproductive surgeries was determined. Samples were taken before (M1), and after antisepsis (M2) and at the end of the surgical procedure (M3) in 12 crossbred bovines aged 12 to 24 months. Trichotomy of the operating field was performed prior to the two antisepsis protocols: 7.5% povidone-iodine and 2% Chlorhexidine Gluconate (both with 3-min contact time and 2-min contact clearance with isopropyl alcohol) and later embrocation with 1% povidone-iodine solution and 0.5% chlorhexidine solution, respectively. The skin swabs were processed by the count technique of colony forming units (CFU/ml). The bacterial load of the two protocols was analysed with the Mann-Whitney-Wilcoxon test for independent samples, without finding significant differences between protocols by evaluation time (p˃0.05). The Friedman test indicated a significant reduction between M1 with M2 and M3 (p<0.05), but not between M2 and M3 (p>0.05).